PEMBERDAYAAN PEREMPUAN MELALUI PENDAMPINGAN BRANDING & PACKAGING KERUPUK PULI DESA KWANGSAN SIDOARJO - Kirana Fasya Juanda Dwi Putri; Yitno Utomo; Dyna Pricilia Hasmiyanti; Anatasya Alfiyah; Affina Damaayu W; Raudah Ferdina; Muhammad Farhan AP (Universitas PGRI Adi Buana Surabaya, 2023)
Empowerment of women is important in individual development. Women are expected to be more efficient, create additional finances for their families, by not leaving their homes.Reaching out for assistance in the Buk Lung business which concentrates on making Puli Calming crackers properly to be able to market the work more broadly. Assistance for SMEs through protecting information about raw materials, training in doing business branding, training in making different packaging according to market needs. Providing supporting facilities in the form of marketing tools, are steps to complete assistance and provide appropriate assistance to women in Kwangsan Village, Sedati District, Sidoarjo Regency